Perencanaan Bahan Baku Sosis Menggunakan Metode Material Requirement Planning (MRP) di PT. RF - Firdaus, Reyhan; Amalia, Akhsani Nur (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to design the planning of sausage raw materials at PT. RF using the Material Requirement Planning (MRP) method. Demand forecasting was carried out using the trend decomposition method for the period of Mei 2025 to April 2026. The forecasting results were used to prepare the Master Production Schedule (MPS) and to calculate raw material needs. The analysis focused on three main raw materials: chicken meat, ice, and seasoning. The results show that the MRP method can accurately determine the quantity and timing of raw material orders according to production needs. The application of this method helps the company avoid shortages or excess inventory and improves the efficiency of procurement and storage processes.